Analisis Teks Berita Kriminal di Surat Kabar Harian Berita Kota Makassar - Andi Rustan (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2023)
This study aims to reveal the representation of: 1) social actors in the text of the crime news in the Makassar City News Daily, and 2) the discourse strategy in the crime news text in the Makassar City News Daily. This research is a descriptive qualitative research. The data sources in this study were newspapers published in the November and December 2019 editions that contained criminal news. The data collection techniques of this research are documentation, snowball technique, and reading quotes. While the data analysis technique in this study was carried out with an interactive analysis model, namely identification, data reduction, data presentation, verification and drawing conclusions. The results showed that: 1) in general, The discourse strategy that is mostly used in crime news texts in the Makassar City News Daily is to bring up social actors and the social actions they take. Marked by mentioning the complete identity in the form of name, occupation, and address. There are also those who do not reveal or hide the identity of social actors; 2) there are eight discourse practices found in the Makassar City News Daily criminal reporting, namely a) 5 exceptions to data;b) allocation of 7 data roles; c) generalization and specification of 4 data; d) assimilation of 2 data, e) dominating association of 20 data; f) uncertainty of 2 data; g) nomination and categorization of 10 data; h) functionalization of 3 data.